Code and compliance: a legal causation framework for fully autonomous weapon systems deployed in urban settings - Kariuki, T. C. (Strathmore University, 2025)
The advancement of fully autonomous weapon systems presents unprecedented legal and ethical challenges, particularly concerning accountability under International Humanitarian Law. These weapons, characterised by deep-learning-led capabilities, can function without direct human intervention, raising concerns about compliance with established norms of warfare. The study explores the necessity of an effective liability framework under International Humanitarian Law for when these weapons inflict harm on protected persons, particularly in urban combat settings. Current legal frameworks within International Humanitarian Law struggle to address accountability gaps introduced by these weapons. The study critically examines the existing liability mechanisms for conventional weapons and weapons of mass destruction, highlighting their inadequacy in dealing with fully autonomous systems. Through an analysis of legal precedents, the study argues that a causation framework exactly like the one in common law negligence—specifically, factual and proximate causation—provides a robust foundation for attributing liability in the context of this study’s problem. Methodologically, this research employs a qualitative deductive approach, drawing from case law, international treaties, scholarly discussions, and more. The study finds that a causation framework exactly like the one in common law negligence should be integrated into International Humanitarian Law to hold users of these weapons (considered to be States) liable for harm they cause in urban areas. In instances where the weaponry is deployed directly to urban areas, liability should be established using the ‘but-for’ test. In cases where it is not deployed to urban areas but takes action within them, the foreseeability test should apply. Ultimately, the study proposes the above integration to ensure the use of these weapons aligns with fundamental humanitarian principles, advocating for judicial interpretation, institutional oversight, and reporting mechanisms to mitigate risks posed by fully autonomous warfare technologies.
Full - text undergraduate research project